2012
DOI: 10.3109/08923973.2011.641971
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal intestinal alteration in experimental colitis correlates with nitric oxide production by peritoneal macrophages: Effect of probiotics and prebiotics

Abstract: Inflammatory bowel disease (IBD) consists mainly of Ulcerative colitis (UC) and Crohn disease (CD). Although its aetiology is still not clearly established, it is thought to be due to overly aggressive immune response to enteric bacteria in genetically predisposed individuals. Manipulating the microbiota using probiotics or prebiotics is considered as a promising field of new therapeutic strategies used to attenuate immune disorders observed during IBD. The production of nitric oxide (NO) seems to be implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
2
29
0
1
Order By: Relevance
“…Thus iNOS might contribute in tissue injury via generation of ONOO Ϫ , and iNOS inhibitors have been shown to reduce colonic damage and inflammation (190). Oral administration of pre-and probiotics in DSS-induced acute murine colitis decreases NO levels in peritoneal macrophages and thus is reported to reduce colonic lesion (2). Further experiments to identify anti-inflammatory properties of probiotics that have been used to treat patients with IBD could determine underlying mechanisms of these potentially beneficial agents.…”
Section: Ibds (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus iNOS might contribute in tissue injury via generation of ONOO Ϫ , and iNOS inhibitors have been shown to reduce colonic damage and inflammation (190). Oral administration of pre-and probiotics in DSS-induced acute murine colitis decreases NO levels in peritoneal macrophages and thus is reported to reduce colonic lesion (2). Further experiments to identify anti-inflammatory properties of probiotics that have been used to treat patients with IBD could determine underlying mechanisms of these potentially beneficial agents.…”
Section: Ibds (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 99%
“…B) RESPIRATORY BURST AND NADPH OXIDASE. Respiratory burst is the process by which phagocytic cells consume large amounts of oxygen during phagocytosis, mainly via activation of NADPH oxidase and release O 2 ·Ϫ into the extracellular space or phagosomes. NADPH oxidase is a multicomponent enzyme present in the plasma membrane and phagosomes of phagocytes such as monocytes, macrophages, neutrophils, and eosinophils (FIGURE 2, Eq.…”
Section: Endogenous Sourcesmentioning
confidence: 99%
“…This observation suggests a possible use of serum NO levels for monitoring disease activity in both types of IBD [16,28,29] . While several studies conducted using animal models indicate the deleterious effect of NO, recent studies have shown that NO may also exert a protective effect against colitis [29][30][31][32] . One study conducted using a DSSinduced colitis model found that nitrite administration exerts both preventive and therapeutic effects in colonic inflammation [33] .…”
Section: No and Ibdmentioning
confidence: 99%
“…There is growing body of evidence that suggest that probiotics and heminths may have potential use as antiinflammatory agents in IBD by inducing antiinflammatory cytokines pattern. The results of our studies and others demonstrated that some probiotics such as Bifidobacterium infantis and Bifidobacterium longum downregulate proinflammatory cytokines IFN-γ, IL-12, TNF-α, and IL-8 production and stimulate immunoregulatory cytokine IL-10 production [33,[90][91][92]. Moreover, it has been reported that B. infantis feeding in DSS-induced colitis model downregulate IL-17A expression and induce IL-10 production restoring thereby the TH17/ Tregs balance [93,94].…”
Section: Therapeutic Implicationsmentioning
confidence: 96%
“…Its expression was mainly detected in lamina propria mononuclear cells and colon epithelial cells of inflamed mucosa [6,12,13,25,[32][33][34]. Studies conducted on a DSSinduced experimental model of colitis in BALB/c mice showed that neutralization of endogenous TNF-α and/or IFN-γ ameliorated the chronic colitis and concomitantly decreased NO generation [32].…”
Section: New Insights Into Inflammatory Bowel Diseasementioning
confidence: 99%